## Let f be a differentiable function. If h(x)=(1+f(3x))2, which of the following gives a correct process for finding h′(x) ?

### To find the derivative of the function h(x)=(1+f(3x))^2, we can use the chain rule

To find the derivative of the function h(x)=(1+f(3x))^2, we can use the chain rule.

The chain rule states that if we have a function g(x) = (f(u))^n, where f(u) is a composite differentiable function and n is a constant, then the derivative of g(x) is given by:

g'(x) = n(f(u))^(n-1) * f'(u) * u’

In this case, our function g(x) is h(x) and f(u) is 1 + f(3x). Let’s break down the steps to find h'(x) using the chain rule:

Step 1: Identify the inner function and the outer function.

The inner function is u = 3x. The outer function is f(u) = 1 + f(3x).

Step 2: Find the derivative of the inner function with respect to x.

The derivative of u = 3x with respect to x is u’ = 3.

Step 3: Find the derivative of the outer function with respect to u.

The derivative of f(u) = 1 + f(3x) with respect to u is f'(u).

Step 4: Substitute the derivatives in the chain rule formula.

Using the chain rule formula, we have:

h'(x) = 2(1 + f(3x))^(2-1) * f'(u) * u’

Step 5: Simplify the expression.

Simplifying further, we have:

h'(x) = 2(1 + f(3x)) * f'(u) * 3

Therefore, the correct process for finding h'(x) is expressed by the following option:

h'(x) = 2(1 + f(3x)) * f'(u) * 3.

##### More Answers:

Finding the Derivative of the Inverse Function | A Step-by-Step Guide with Example CalculationFinding the Slope of a Tangent Line | Step-by-Step Guide with Example

Finding dy/dx for the equation sin(x + y) = 3x – 2y using the chain rule